2018
DOI: 10.3390/molecules23092305
|View full text |Cite
|
Sign up to set email alerts
|

Phenethyl Isothiocyanate Inhibits In Vivo Growth of Xenograft Tumors of Human Glioblastoma Cells

Abstract: Phenethyl isothiocyanate (PEITC) from cruciferous vegetables can inhibit the growth of various human cancer cells. In previous studies, we determined that PEITC inhibited the in vitro growth of human glioblastoma GBM 8401 cells by inducing apoptosis, inhibiting migration and invasion, and altering gene expression. Nevertheless, there are no further in vivo reports disclosing whether PEITC can suppress the growth of glioblastoma. Therefore, in this study we investigate the anti-tumor effects of PEITC in a xenog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…Similarly, our previous study [ 34 ] also reported a marked reduction in tumorigenicity and metastasis in mice that had received a PEITC-treated hCSCs. These observations warrant a large-scale efficacy study in the future, similar to that reported by other colleagues [ 45 , 46 ]. Altogether, the animal study helped to further support our in vitro data on effects of PEITC targeting ALDH1 hi hCSCs tumorsphere formation.…”
Section: Discussionsupporting
confidence: 89%
“…Similarly, our previous study [ 34 ] also reported a marked reduction in tumorigenicity and metastasis in mice that had received a PEITC-treated hCSCs. These observations warrant a large-scale efficacy study in the future, similar to that reported by other colleagues [ 45 , 46 ]. Altogether, the animal study helped to further support our in vitro data on effects of PEITC targeting ALDH1 hi hCSCs tumorsphere formation.…”
Section: Discussionsupporting
confidence: 89%
“…Phenethyl isothiocyanate (PEITC) is formed upon hydrolysis of the parent glucosinolates, which occurs in cruciferous vegetables including cabbage, kale, broccoli, and Brussels sprouts (Park et al., 2017). In vivo and in vitro studies have shown that PEITC regulates cancer‐related gene expression, such as antioxidant response, resistance to apoptosis, cell cycle regulation, and metastasis (Chou et al., 2018; Lam‐Ubol et al., 2018). Furthermore, in our previous study, we showed that PEITC supplementation in high fat/cholesterol diet‐fed mice reduced fat/cholesterol accumulation in the liver and aorta and decreased liver HFCD‐related inflammation (Gwon et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Consumption of ITCs can positively affect human health as they have antimicrobial, antidiabetogenic, chemopreventive, and anticarcinogenic properties [ 8 , 9 ]. Previous studies have shown a positive correlation between ITC uptake and cancer prevention [ 8 , 10 , 11 ], and especially 4-(methylsulfinyl)butyl ITC (sulforaphane; 4MSOB-ITC) is valued for its anticarcinogenic potential [ 8 ]. Simple nitriles and ETNs on the other hand, seem to have less health beneficial effects [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%